Psychometric characteristics for attachment styles among a sample of secondary school students in Buraidah city - Al-Qusayer, Nafla Sulaiman; Al-Rebdi, Sufyan Ibrahim (Journal of Educational and Psychological Sciences, 2023)
This study aimed to investigate the psychometric characteristics of the attachment styles scale. The study used the descriptive methodology since it is suitable for the objective of the study. The total sample of the study was (130) high school male and female students in Buraydah city. Where the scale is in its initial formed of (32) items distributed on four main dimensions, which are (Secure attachment, Preoccupied Attachment, Fearful Attachment, Dismissing Attachment). It was confirmed that the psychometric properties of the scale were achieved by using appropriate statistical treatments to come up with the final form of the scale, as it settled on (23) items distributed on the four dimensions of the attachment styles with good psychometric properties in terms of construction, honesty and stability.
Keywords: attachment style; high school students; psychometric characteristics